Language Diplomacy Through BIPA: An Indonesian Language Training Program For NEUST Philippines Students - Nur Lailatul Aqromi; Suastika Yulia Riska; Emilsa T. Bantug; Chyndy Febrindasari (International Journal Of Community Service, 2025)
This community engagement program was initiated in response to the linguistic needs of foreign students from the Nueva Ecija University of Science and Technology (NEUST), Philippines, who required Indonesian language proficiency to participate effectively in a student exchange program with the Institute of Technology and Business Asia Malang, Indonesia. The partner institution faced two primary challenges: the absence of a practical and systematic Indonesian language training program for foreign learners and the limited initial language competence among NEUST students. Interestingly, structural similarities between Tagalog and Indonesian—particularly in basic morphemes and affixation patterns—offered a promising foundation for language acquisition. The program aimed to introduce fundamental Indonesian language proficiency equivalent to BIPA Level 4, focusing on communicative competence in academic and social contexts. It was conducted online through five sessions, including one orientation, four core training sessions based on the Task-Based Language Teaching (TBLT) approach, and one evaluation session. The learning materials were adapted from Sahabatku Indonesia – BIPA 4, published by the Ministry of Education and Culture. The outcomes demonstrated significant improvement in participants’ linguistic competence, reflected in higher evaluation scores and active engagement throughout the training. Additional outcomes included online media publications and the adoption of the developed modules as sustainable BIPA teaching materials at NEUST. Overall, this initiative represents an effort in Indonesian language diplomacy, contributing to the strengthening of academic mobility and intercultural collaboration across Southeast Asia.